Analisis Efisiensi Penggunaan Tempat Tidur dengan Barber Johnson Chart di RSUD Dr. Soekardjo Tasikmalaya Tahun 2022–2024 - Tiara Islamiah Zaenal; Chindy Maria Orizani; Silvia Haniwijaya Tjokro; Yura Witsqa Firmansyah (Jurnal Kesehatan Holistic, 2026)
Bed utilization efficiency was an important indicator in assessing the quality of hospital services. An evaluation of efficiency was required to ensure that the availability of beds could be optimally used by patients in need. This study aimed to analyze the efficiency of inpatient bed utilization at Dr. Soekardjo General Hospital, Tasikmalaya, in 2022–2024 using the Barber Johnson chart. A quantitative study with a retrospective design and secondary data analysis from hospital medical records for the years 2022-2024. The analyzed indicators included Bed Occupancy Rate (BOR), Average Length of Stay (AvLOS), Turn Over Interval (TOI), and Bed Turn Over (BTO). The results were compared with the efficiency standards of the Indonesian Ministry of Health (2012). The results showed that BOR ranged from 48.12% to 53.02%, AvLOS from 4.40 to 4.97 days, TOI from 4.04 to 4.49 days, and BTO from 41.48 to 45.07 times. All indicators were outside the standard except BTO, which approached the ideal value. The Barber Johnson chart demonstrated that during the 2022–2024 period, the hospital had not reached optimal efficiency, although there was temporary improvement in 2023. This study concluded that inpatient bed utilization efficiency at Dr. Soekardjo General Hospital, Tasikmalaya, had not met the Barber Johnson standards. Optimization strategies were needed through improving BOR, adjusting the length of stay, and enhancing patient flow management to reduce TOI and achieve better inpatient service efficiency.